The Effect of Entrepreneurial Orientation on Social Media Adoption and Business Performance Moderated by Innovation Capability in Healthy Food SMEs in DKI Jakarta - Felisia Natasha; Lelly Christin; Ferdinandus Winandy Soesilo (Journal of Accounting and Finance Management, 2023)
Social media has facilitated many people on following healthy lifestyle trend. Consequently, those involved in the food industry should be able to see this as an opportunity to improve performances. This research was conducted on healthy food businesses in DKI Jakarta with the aim of looking at the effect of entrepreneurial orientation, social media adoption, and the ability to innovate on the performance of MSMEs with the adoption of social media as a mediating variable and innovation ability as a moderating variable. This study used a quantitative method with a total of 162 respondents who collected questionnaires and used Smart-PLS 3.3 to test the data. The result of the study shows that entrepreneurial orientation and social media adoption have a significant effect on the performance of MSMEs. Entrepreneurial orientation has a significant influence on the performance of MSMEs which is mediated by the adoption of social media. Entrepreneurial orientation has a significant influence on social media adoption. The ability of innovation does not have a significant effect on the performance of SMEs. Adoption of social media does not have a significant effect on the performance of MSMEs, which is moderated by the ability to innovate.